2019
DOI: 10.9734/ijtdh/2019/v37i330166
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Tuberculosis in Children in Port Harcourt – A Worrisome Trend

Abstract: Background: Drug-resistant tuberculosis and multidrug-resistant tuberculosis (MDR-TB) in particular represent a major threat to the fight against tuberculosis globally. MDR-TB presents with similar features and is transmitted in the same way as drug sensitive TB but its progression is rapid and its treatment, associated drug toxicity and monitoring constitute a heavy burden to the patients and the health system. MDR-TB affect people of all age groups but very little is known about the magnitude of this problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 10 in Addis Ababa and Ide et al . 13 in Port Harcourt, they found the prevalence levels of 7.9% and 10.8%, respectively, in their studied children population. Drug-resistant TB is rarely reported among toddlers in Nigeria.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“… 10 in Addis Ababa and Ide et al . 13 in Port Harcourt, they found the prevalence levels of 7.9% and 10.8%, respectively, in their studied children population. Drug-resistant TB is rarely reported among toddlers in Nigeria.…”
Section: Discussionmentioning
confidence: 83%
“… 13 reported four cases of MDR-TB among children whose ages ranged from 3 months to 24 months; the authors observed positive history of contact in all the patients who belong to low socioeconomic class. Previous treatment for TB is the strongest risk factor for the development of MDR-TB; 5 10 12 13 14 this is partly due to acquired drug resistance which emanates from poor compliance to dose and duration of treatment, substandard drugs, and the absence of infection control measures in hospitals. Resistance to anti-TB medications is due to mutations in the drug target genes of the bacterial chromosome before the strains are exposed to the drugs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation